PELATIHAN BERBAHASA INGGRIS DENGAN DRILLING DAN REPETITION BAGI KARANG TARUNA DESA JEDONG - Andy, Andy; Rusfandi, Rusfandi; Muzammil, Lasim (Universitas Muhammadiyah Tapanuli Selatan, 2018)
From the result of situation analysis and partner’s problem, pengabdi (society service) team gives a solution to enlarge the opportunity for karangtaruna (youth association) to be accepted to work upon the graduation of Vocational High School. The solution is formulated in the form of a workshop and coaching for karangtaruna members (youth association) to practice English verbal proficiency by drilling and repetition method. At the end of this society service, the results are (1) Positive response and enthusiasm from youth association in Jedong village Wagir district. (2) Improved awareness of the benefit of English verbal proficiency. (3) Willingness to take a risk in participating. (4) Improved glossary, grammar, pronunciation,and spelling of verbal English and not ambiguous. (5) Improved chance to listen to native speaker’s voice recording. (6) Improved chance to practice verbal English in the monologue (self-introduction), in pairs and mingle (talking in turns with all participants in a dynamic and fun/not boringatmosphere. (7) Learning media with mp3 native speaker voice recording becomes available. (8) Youth association members can be facilitated to listen to native speaker’s voice recording, imitating and independent self-practice in their spare time. (9) Online webs become accessible to browse and download learning media files for future learning after this society service comes to its end. Keywords:Drilling and Repetition, Improving Verbal English Proficiency.